Healing and coping with life within challenges of spiritual insecurity: Juxtaposed consideration of Christ"s sinlessness and African ancestors in pastoral guidance - Magezi, Vhumani (HTS teologiese studies, 2017)
Spiritual insecurity among African Christians is a huge challenge. The insecurity among other things arises from African people’s former traditional African ancestral world view of ancestral veneration. The ancestors promote or hinder African Christians’ reliance on Christ because they have presupposedly acquired the supernatural power that enables them to provide diagnoses and solutions to life challenges. The inherent problem in the ancestral world view, however, is that the ancestors are both respected and feared by their descendants because they can either bless or harm depending on the state of the relationship between the surviving human beings and the ancestors. The basis of the unpredictable influence of ancestors lies in the fact that they (ancestors) are considered as human beings who carry their human qualities to the spiritual world. In light of this situation, one constructive approach that can be advanced to address the challenges of African Christians’ spiritual insecurity is a proper understanding of Christ as a sinless representative of humanity. This approach maintains that healing and coping with life within the challenge of African spirituality in the context of threatening life issues can be addressed by an appropriate understanding of Christ’s sinlessness. The article argues for the foundational status of Christ as a sinless representative of humanity as the controlling framework. In doing so, Christ’s sinlessness and the sinfulness of natural ancestors are juxtaposed to compare the two ontologies in order to draw some pastoral guidelines for African Christians. This approach pays close attention to the factors and mindset that sustain people who adhere to ancestral worship and assess them through a lens of Christology focusing on Christ’s sinlessness as an exemplary doctrine.